Disinformation for Hire: Examining the Production of False COVID-19 Information - Alain Cohn; Jan Stoop; Hatim A. Rahman (Tinbergen Institute, 2022)
Misinformation is linked to increased social divisions and adverse health outcomes. While most research focuses on the spread of misinformation, we examine the production of misinformation intended to mislead (disinformation). Our field experiment (N=1,200) found, adjusting for circumstantial factors, 87% of workers in an online labor market completed a job requesting them to create a misleading COVID-19 graph. Viewing a disinformation graph from the experiment negatively affected people's beliefs and behavioral responses to the COVID-19 pandemic, including increased vaccine hesitancy. Using a "wisdom-of-crowds" approach, we highlight how online labor markets can introduce features that may reduce the production of disinformation.
Keywords: C93; D91; J22; 330; disinformation; field experiment; online labor markets; immoral work